4′-C-Trifluoromethyl modified oligodeoxynucleotides: synthesis, biochemical studies, and cellular uptake properties12. Issue 22 (21st May 2019) - Zhou, Yifei; Zang, Chuanlong; Wang, Huawei; Li, Jiajun; Cui, Zenghui; Li, Qiang; Guo, Fengmin; Yan, Zhiguo; Wen, Xin; Xi, Zhen; Zhou, Chuanzheng
Abstract : Introducing a 4′-C-trifluoromethyl (4′-CF3 ) modification into oligodeoxynucleotides (ODNs) leads to improved nuclease resistance and increased cell permeability. Abstract : Herein, we report the synthesis of 4′-C-trifluoromethyl (4′-CF3 ) thymidine (T 4′-CF3 ) and its incorporation into oligodeoxynucleotides (ODNs) through solid-supported DNA synthesis. The 4′-CF3 modification leads to a marginal effect on the deoxyribose conformation and a local helical structure perturbation for ODN/RNA duplexes. This type of modification slightly decreases the thermal stability of ODN/RNA duplexes (−1 °C/modification) and leads to improved nuclease resistance. Like the well-known phosphorothioate (PS) modification, heavy 4′-CF3 modifications enable direct cellular uptake of the modified ODNs without any delivery reagents. This work highlights that 4′-CF3 modified ODNs are promising candidates for antisense-based therapeutics, which will, in turn, inspire us to develop more potent modifications for antisense ODNs and siRNAs.